2007
DOI: 10.1063/1.2561032
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting devices with transparent single-walled carbon nanotube electrodes

Abstract: Microfluidic devices based on the electrowetting principle, more specifically electrowetting on dielectric, were fabricated using transparent single-walled carbon nanotube films as electrodes. The films were spray coated on glass and polyethylene terephalate substrates. The transmittance and sheet resistance remain unchanged after patterning the films using typical photolithography and plasma etching. Operation of water droplets over the patterned nanotube electrodes was demonstrated, and the performance was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 12 publications
2
55
0
Order By: Relevance
“…16 Briefly arc-discharged single wall nanotube ͑Carbon Solutions Inc.͒ are dispersed in water with 0.5% sodium dodecyl sulfate with surfactants of 1 mg/ ml. The solutions were sprayed onto glass or plasticsubstrates which were then heated to 80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Briefly arc-discharged single wall nanotube ͑Carbon Solutions Inc.͒ are dispersed in water with 0.5% sodium dodecyl sulfate with surfactants of 1 mg/ ml. The solutions were sprayed onto glass or plasticsubstrates which were then heated to 80°C.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, we have used a very well established technique of depositing uniform, highly conductive SWCNT films on large areas a͒ These two authors contributed equally to this work. through spray coating 16 and combined the benefits of that method with a bottom-up LbL approach for highly stable EC devices.…”
Section: Introductionmentioning
confidence: 99%
“…SWNT thin films with thickness in the range of 10-100 nm can have low sheet resistance and high optical transparency as well as robust mechanical flexibility [26]. SWNT thin films have been demonstrated in devices including solar cells [27], thin film transistors [28], light emitting diodes [29], and electrowetting [30]. Recent researches suggested that the electrical stability and mechanical robustness of SWNT films could be improved by embedding SWNT thin film into polymers [31][32][33].…”
Section: Swnt-embedded Pdms Thin Film Electrodementioning
confidence: 99%
“…To date, the TFC electrodes are mostly based on PE-DOT [36,70,74,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], graphene (GF) [73,75,[99][100][101][102][103][104][105][106][107][108][109][110][111][112], carbon nanotubes (CNTs) [73,101,102,[106][107][108][109]113], Ag-based nanowires/grids/films [72,[114][115][116][117][118][119]…”
Section: Design Of Flexible Electrodesmentioning
confidence: 99%